Diversity of Fishermen Catches in Fishing Port of Sungai Raya Kepulauan in Bengkayang District - Agus Agus; inpurwanto inpurwanto; yeni hurriyani (Jurnal Sains Pertanian Equator, 2020)
Sungai Raya Kepulauan Sub-district is a coastal area located on the north coast of West Kalimantan bordered by the South China Sea and Natuna Sea. This sub-district has three Fishing Port namely, TPI Sungai Keran, TPI Sungai Raya, and TPI Karimunting. This research aims to identify the diversity index, uniformity index, dominance index, and composition of fishermen catches in TPI Sungai Raya Kepulauan, Bengkayang District. It used census method for the determination of collectors. The research was conducted in October - January 2020. The research found that the catches in TPI Sungai Raya Kepulauan covered of 34 fish species consisting of 17 families, namely Aridae, Balistidae, Caesionidae, Clupeidae, Dasyatidae, Gymnuridae, Haemulidae, Lethridae, Lethridae , Lutjanidae, Mullidae, Nemipteridae, Polynemidae, Rachycentridae, Scombridae, Serranidae, and Sphyraenidae with a total of 4991 fishes. The composition of fish species in the three stations was the highest, namely mackerel fish (Rastrelliger kanagurta) 10.82%, kerisi fish (Nemipterus furcocus) 9.84% and geronggong  fish (Megalasfis cordyla) 8.76%.The diversity index (H’) covered moderate to high categories with a value of 2.947 – 3.079, while the uniformity index value ranges from 0.850 –0.886 in the high category. The last, the dominance index (C) value ranges from 0.059 – 0.069 in the low category.